EBI-3 Chain of IL-35 Along With TGF-β Synergistically Regulate Anti-leishmanial Immunity - Asad, Mohammad; Sabur, Abdus; Shadab, Mohammad; Das, Sonali; Kamran, Mohd.; Didwania, Nicky; Ali, Nahid (Frontiers in Immunology, 2019)
Immuno-suppression is a characteristic feature of chronic leishmaniasis. The dynamicity and the functional cross talks of host immune responses during Leishmania infection are still not clearly understood. Here we explored the functional aspects of accumulation of immune suppressive cellular and cytokine milieu during the progression of murine visceral leishmaniasis. In addition to IL-10 and TGF-β, investigation on the responses of different subunit chains of IL-12 family revealed a progressive elevation of EBI-3 and p35 chains of IL-35 with Leishmania donovani infection in BALB/c mice. The expansion of CD25 and FoxP3 positive T cells is associated with loss of IFN-γ and TNF-α response in advanced disease. Ex-vivo and in-vivo neutralization of TGF-β and EBI-3 suggests a synergism in suppression of host antileishmanial immunity. The down-regulation of EBI-3 and TGF-β is crucial for re-activation of JAK-STAT pathway for induction as well as restoration of protective immunity against L. donovani infection.